BUMDesa Performance Ranking Analysis in Kampar Regency Based on Kepmendesa No. 145/2022 - Amanda Novawati Theresia; Dewi Ellyssa Afriani Lubis; Donna Suryani Malau; M. Fachry Alfhanza; Trilian Febrianti Gulo; Taryono (Jurnal Ilmiah Ekonomi dan Keuangan, 2026)
This study aims to analyze the performance of Village-Owned Enterprises (BUMDesa) based on four national ranking categories Pioneer, Beginner, Developing, and Advanced in Kampar Regency, Riau Province, using the indicators of Ministerial Decree No. 145 of 2022. A descriptive qualitative case study approach was employed, examining four representative BUMDesa: BUMDesa Permata Sakti Aursati (Pioneer), BUMDesa Koto Sepakat (Beginner), BUMDesa Teratai Kelulut (Developing), and BUMDesa Kampung Patin (Advanced) Data were sourced from data.go.id, Satu Data Kampar, and recent academic literature. Most BUMDesa in Kampar Regency remain in the Pioneer (76 units) and Developing (100 units) categories. Key barriers include limited institutional capacity, non-professional management, limited capital, minimal external partnerships, and low financial reporting accountability. This study provides empirical analysis based on the Kepmendesa 145/2022 ranking indicators and Business Model Canvas (BMC) as a transformation framework for BUMDesa toward the Advanced category. Structured assistance through simple management audits, administrative digitalization, and strengthening strategic partnerships is needed.